Gaya Kepemimpinan Transformasional dan Transaksional Serta Dampaknya Terhadap Kepuasan Kerja Karyawan - faizal roni (Widya Cipta - Jurnal Sekretari dan Manajemen, 2019)
The Goal of this study are to assess, analyze, and appointment of empirically the effects of Transformational Leadership and Transactional Leadership on Employee satifaction Yayasan Khazanah Kebajikan in south Tangerang City. This study uses data from the Associative Primary Questioner. The sample size is determined by the formula “Slovin the total sample are 130 respondents of 200 employees. The Technical of analysis is a descriptive statistical analysis. This study examined the leadership style with two variabels as Independent variabel to the satisfaction of working with one variable as Dependent Variabel, that is : Transformational Leadership (X1) and Transactional leadeship (X2) as Independent Variabel , job satisfaction (Y) as the Dependent Variabel. These three variable were tested by partial dan simultaneously, immediate effect Partial assay results are as follows : The effect of Transformational Leadership style on job satisfaction isvariables have positive and significant effect, The effect of Transactional Leadership style on job satisfaction is variables have positive and significant effect, and simultaneous test are as follows : The effect of Transformational and Transactional Leadership style on job satisfaction is variables have positive and significant effect.